A novel circular fractal ring UWB monopole antenna with dual band-notched characteristics - Kayhan Celik (ETRI Journal, 2024)
This paper presents a novel circular fractal ring monopole antenna for ultra-wideband (UWB) hardware with dual band-notched properties. The proposed antenna consists of four crescent-shaped nested rings, a tapered feeding line at the front of the dielectric material, and a semicircular ground plane on the backside. In this design, the nested rings are used both as a radiation element and a band rejection element. The proposed antenna has a bandwidth of 9.03 GHz, which works efficiently in the range of 2.63 GHz-11.66 GHz with the dual notched bands of Worldwide Interoperability for Microwave Access (WiMAX) at 3.15 GHz-3.66 GHz and wireless local area network (WLAN) at 4.9 GHz-5.9 GHz, respectively. The antenna has a compact size of 20 mm X 30 mm X 1 mm (0.177 X 0.265 X 0.0084 λ0) and is implemented using a flame-retardant type 4 (FR4) material. It has a maximum gain of approxi-mately 4 dB in its operating range, and experimental results support the simu-lation predictions with high accuracy. The findings of this study imply that the designed antenna can be utilized in UWB applications.